2014
DOI: 10.1128/mcb.00023-14
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Gene Editing by Injection of mRNAs Encoding Transcription Activator-Like Effector Nucleases into Mouse Zygotes

Abstract: Injection of transcription activator-like effector nucleases (TALEN) mRNAs into mouse zygotes transferred into foster mothers efficiently generated founder mice with heritable mutations in targeted genes. Immunofluorescence visualization of phosphorylated histone 2A (␥H2AX) combined with fluorescence in situ hybridization revealed that TALEN pairs targeting the Agouti locus induced site-directed DNA breaks in zygotes within 6 h of injection, an activity that continued at reduced efficiency in twocell embryos. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
3
15
0
Order By: Relevance
“…The mosaicism was subsequently confirmed by sequencing of the Rosa26 locus in F1 generation mice (not shown). This indicates nuclease activity in later than the one-cell stage, as was recently described by Li and colleagues, who observed simultaneous gene editing in zygotes using TALENs [20]. This phenomenon could affect all nucleases Among Rosa26-TurboRFP founders, we identified 2 correctly targeted animals (R6 and R15) and one mouse with partial integration of the targeting vector (R8), which had lost a portion of the TurboRFP gene.…”
Section: Discussionsupporting
confidence: 74%
“…The mosaicism was subsequently confirmed by sequencing of the Rosa26 locus in F1 generation mice (not shown). This indicates nuclease activity in later than the one-cell stage, as was recently described by Li and colleagues, who observed simultaneous gene editing in zygotes using TALENs [20]. This phenomenon could affect all nucleases Among Rosa26-TurboRFP founders, we identified 2 correctly targeted animals (R6 and R15) and one mouse with partial integration of the targeting vector (R8), which had lost a portion of the TurboRFP gene.…”
Section: Discussionsupporting
confidence: 74%
“…Continued breeding from these chimeric G1 H2A.B.3 --/x females with wt males (up to 4 generations), revealed that these additional mutations were lost after G2, but maintained original founder mutations (H2Afb3 X ∆+286 , gm14290 X ∆15 , H2Afb2 X ∆17 ). This can be explained by the fact that TALEN activity can be retained for several cell divisions following their injection into the 2--cell stage, thus producing a mosaic genotype, as previously observed 14,15 . Collectively, the G1 generation of the 9 founder Table 3).…”
Section: H2ab3 Genes (Supplementarymentioning
confidence: 68%
“…RNAs encoding forward and reverse TALEN nucleases directed to spacer sequences flanking the first Arf ATG codon were injected into C57BL/6J × FvN/N mouse zygotes and yielded mosaic pups in which a 25-bp deletion, including the 5′ ATG, generated a frame-shift mutation in which translation was initiated at M45 (19). A second strain with a single base-pair deletion immediately 3′ to the first ATG similarly initiated translation at M45 and was indistinguishable from the first.…”
Section: Generation Of Mouse Strains Expressing Either P19 Arf or P15mentioning
confidence: 99%